CERTIFICATION OF OLD-AGED AND YARD TREES AND THE PROVISION OF ECONOMIC INCENTIVES FOR OWNERS AS A FAIR COMPENSATION FOR ENVIRONMENTAL SUSTAINABILITY GUARDIANS - Tb. MA. Rahmatullah; Medy Susanto (Proceeding International Conference on Social Sciences, 2026)
Efforts to maintain environmental quality are mandated for both the state and its citizens under the 1945 Constitution of Indonesia, particularly Article 28H and Article 33 paragraph (4). These principles align with the global Sustainable Development Goals (SDGs), especially in protecting the environment through the conservation of old-aged trees and privately owned yard trees. This paper examines the necessity of establishing a certification framework for such trees as a legal foundation for granting financial incentives to their owners. These incentives are viewed as a fair recognition of their contributions to clean air provision, carbon absorption, ecological stability, and the prevention of illegal logging. Using a normative juridical method supported by statutory, conceptual, and comparative approaches, this study reveals the absence of any regulations that specifically address legal protection or economic benefits for tree owners outside state forest zones. Certification of individual trees may function as a legal innovation consistent with ecological justice and green economy principles. Implementing this certification mechanism could form the basis for measurable and fair fiscal incentives or environmental compensation. Ultimately, this policy strengthens public legal awareness and supports long-term environmental sustainability.